Quantitative spectrophotometric estimation of specific monosaccharides by DNSA method - Rajbhar, Karishma; Dawda, Himanshu; Mukundan, Usha (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The determination of saccharide is widespread and has led to the development of numerousanalytical techniques for measuring its concentrations. Analytical tool with various applicationsin different fields are tedious and have time-consuming protocols ranging from food analysisto biology. The overall purpose of this research is to develop easy methods for analyzingreducing sugars or saccarides. The most abundant monosaccharide in nature Dglucosesometimes referred to as dextrose in our research its shows a peak difference of 1nm as onewater molecule is always loosely attached to dextrose ring structure. In this article it is seenthat DNSA methods has advantage of its simplicity, low cost, sensitivity and adoptableduring handling the analysis of a large number of samples at a time.